2014
DOI: 10.1111/mmi.12571
|View full text |Cite
|
Sign up to set email alerts
|

Genetically distinct pathways guide effector export through the type VI secretion system

Abstract: Summary Bacterial secretion systems often employ molecular chaperones to recognize and facilitate export of their substrates. Recent work demonstrated that a secreted component of the type VI secretion system (T6SS), hemolysin co-regulated protein (Hcp), binds directly to effectors, enhancing their stability in the bacterial cytoplasm. Herein, we describe a quantitative cellular proteomics screen for T6S substrates that exploits this chaperone-like quality of Hcp. Application of this approach to the Hcp secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
252
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(261 citation statements)
references
References 65 publications
(104 reference statements)
8
252
0
1
Order By: Relevance
“…rearrangement hotspot (Rhs) repeat protein. Rhs and related YDrepeat proteins deliver toxic nuclease domains into both Gramnegative and Gram-positive bacteria (32,33). Further, the Ntox28 homolog from Geobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…rearrangement hotspot (Rhs) repeat protein. Rhs and related YDrepeat proteins deliver toxic nuclease domains into both Gramnegative and Gram-positive bacteria (32,33). Further, the Ntox28 homolog from Geobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The striking conservation of genetic modules encoding homologous VgrG, a distinct set of potential adaptor/chaperone, and a specific effector in various Proteobacteria strongly suggest a conserved mechanism in type VI effector delivery. (30,31). Recent studies further identified a DUF4123-domaincontaining protein, Tap-1/Tec, that is required for loading a specific effector onto cognate VgrG for delivery in V. cholerae (32,33).…”
Section: Significancementioning
confidence: 99%
“…The T6 apparatus is a multiprotein, cell envelope spanning complex comprised of core Tss proteins. A key component of the machinery is a needle-like structure, similar to the T4 contractile bacteriophage tail, which is assembled in the cytoplasm where it is loaded with toxic effectors (8)(9)(10). Contraction of the sheath surrounding the needle apparatus drives expulsion of the needle from the cell, delivering the needle and associated effectors either into the supernatant of in vitro grown bacteria, or across the membrane of prey cells.…”
mentioning
confidence: 99%